Fostering Pupils’ English Learning Motivation through a Local Wisdom-Integrated Problem-Based Learning Model: A Quasi-Experimental Study - Kholida Hirziana Rusnaleli Rusnaleli; Indri Yani; Elly Sukmanasa (MASI Mandiri Edukasi, 2026)
Integrating local wisdom into English instruction is a crucial step in creating meaningful, relevant learning experiences for pupils in the 21st century. The objective of this study, which uses a quantitative method with a Quasi-Experimental Design, is to determine the significance of the local wisdom-based PBL model in increasing primary school pupils' learning motivation in the English subject. Although the PBL model has been widely studied as an effective learning model that can increase pupils’ motivation to learn, there remains a significant research gap in the number of studies examining the integration of local wisdom values into the PBL model in the context of English learning in primary schools. A 21-item questionnaire, aligned with learning motivation indicators, was used as the primary instrument to collect primary data in this study. The paired sample t-test and the N-Gain test were used in this study as data analysis techniques. The results of this study indicate that the PBL model significantly increases pupils’ motivation to learn in the English subject. The sig illustrates this. value in the experimental class is <0.000, and the N-Gain score of 0.7658 is in the high category. The main contribution of this study is the development of a PBL learning model integrated with Sundanese local wisdom values, which are still relatively new in English subjects in primary schools.